Teaching and learning mathematics in a bilingual situation - BAGNI, GIORGIOT.; CECCHINI, CARLO; COPETTI, FRANCESCA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2006)
The aim of this paper is to show how an experiment in teaching maths in both Italian and Friulian in a primary school supports the classical ideas of Vygotskij on the development of language.